DIET-like mutualism of Geobacter and methanogens at specific electrode potential boosts production of both methane and hydrogen from propionate. (15th May 2023) - Yan, Yuqing; Zhang, Jiayao; Tian, Lili; Yan, Xuejun; Du, Lin; Leininger, Aaron; Zhang, Mou; Li, Nan; Ren, Zhiyong Jason; Wang, Xin
Highlights: Hydrogen and methane were both boosted in anaerobic electrochemical digestion. Anodic electrogen Geobacter were drastically enriched in planktonic microbiome. Metagenomic analysis suggested a possible methanogenic direct electron transfer. Hydrogen and bioelectricity were necessary to trigger the DIET-like mutualism. Methanothrix and Methanosarcina may participate in DIET. Abstract: Direct interspecies electron transfer (DIET) has been demonstrated to be an efficient type of mutualism in methanogenesis. However, few studies have reported its presence in mixed microbial communities and its trigger mechanism in the natural environment and engineered systems. Here, we reported DIET-like mutualism of Geobacter and methanogens in the planktonic microbiome for the first time in anaerobic electrochemical digestion (AED) fed with propionate, potentially triggered by excessive cathodic hydrogen (56 times higher than the lowest) under the electrochemical condition. In contrast with model prediction without DIET, the highest current density and hydrogen and methane production were concurrently observed at −0.2 V where an abundance of Geobacter (49%) and extracellular electron transfer genes were identified in the planktonic microbiome via metagenomic analysis. Metagenomic assembly genomes annotated to Geobacter anodireducens were identified alongside two methanogens, Methanothrix harundinacea and Methanosarcina mazei, which were previously identified to participate in DIET. This discovery revealed that DIET-like mutualism could be triggered without external conductive materials, highlighting its potentially ubiquitous presence. Such mutualism simultaneously boosted methane and hydrogen production, thereby demonstrating the potential of AED in engineering applications. Graphic abstract: Image, graphical abstract